The document presents the derivation of the integration by parts formula. It shows that the formula can be derived by taking the derivative of the product of two functions f(x) and g(x), and then integrating both sides. This results in the integration by parts formula: the integral of f(x)g(x)dx is equal to f(x)g(x) - the integral of f'(x)g(x)dx. An example is then given of using integration by parts to calculate the integral of xcosxdx.
1 of 7
Download to read offline
More Related Content
Cálculo II - Aula 3: Integração por partes
1. Observe que x 2 dx = xdx · xdx
Willian Vieira de Paula Aula 3 - Integra¸˜o por partes
ca
2. d
dx [f (x)g (x)] = f (x)g (x) + f (x)g (x)
Willian Vieira de Paula Aula 3 - Integra¸˜o por partes
ca
3. d
dx [f (x)g (x)] = f (x)g (x) + f (x)g (x)
d
“Integrando” dx [f (x)g (x)] dx = [f (x)g (x) + f (x)g (x)] dx
Willian Vieira de Paula Aula 3 - Integra¸˜o por partes
ca
4. d
dx [f (x)g (x)] = f (x)g (x) + f (x)g (x)
d
“Integrando” dx [f (x)g (x)] dx = [f (x)g (x) + f (x)g (x)] dx
d
f (x)g (x)dx = dx [f (x)g (x)] dx − f (x)g (x)dx
Willian Vieira de Paula Aula 3 - Integra¸˜o por partes
ca
5. d
dx [f (x)g (x)] = f (x)g (x) + f (x)g (x)
d
“Integrando” dx [f (x)g (x)] dx = [f (x)g (x) + f (x)g (x)] dx
d
f (x)g (x)dx = dx [f (x)g (x)] dx − f (x)g (x)dx
Portanto f (x)g (x)dx = f (x)g (x) − f (x)g (x)dx
Willian Vieira de Paula Aula 3 - Integra¸˜o por partes
ca
6. Exemplo: Calcule, usando integra¸˜o por partes:
ca
xcosxdx
Willian Vieira de Paula Aula 3 - Integra¸˜o por partes
ca
7. ¸˜
INTEGRACAO POR PARTES
udv = uv − vdu
Willian Vieira de Paula Aula 3 - Integra¸˜o por partes
ca